Relationship between Length and Surface-Enhanced Raman Spectroscopy Signal Strength in Metal Nanoparticle Chains: Ideal Models versus Nanofabrication. (11th April 2012) - Alexander, Kristen D.; Zhang, Shunping; Hight Walker, Angela R.; Xu, Hongxing; Lopez, Rene
Abstract : We have employed capillary force deposition on ion beam patterned substrates to fabricate chains of 60 nm gold nanospheres ranging in length from 1 to 9 nanoparticles. Measurements of the surface-averaged SERS enhancement factor strength for these chains were then compared to the numerical predictions. The SERS enhancement conformed to theoretical predictions in the case of only a few chains, with the vast majority of chains tested not matching such behavior. Although all of the nanoparticle chains appear identical under electron microscope observation, the extreme sensitivity of the SERS enhancement to nanoscale morphology renders current nanofabrication methods insufficient for consistent production of coupled nanoparticle chains. Notwithstanding this fact, the aggregate data also confirmed that nanoparticle dimers offer a large improvement over the monomer enhancement while conclusively showing that, within the limitations imposed by current state-of-the-art nanofabrication techniques, chains comprising more than two nanoparticles provide only a marginal signal boost over the already considerable dimer enhancement.